Portrait of the economist as a young man: Raúl Prebisch's evolving views on the business cycle and money, 1919-1949 - Esteban Pérez Caldentey; Matías Vernengo (The University of Utah, Department of Economics, 2011)
This paper analyzes Raúl Prebisch's less familiar contributions to economic theory, related to the business cycle, and heavily informed by the Argentinean experience. His views of the cycle emphasize the common nature of the cycle in the center and the periphery as one unified phenomenon. While his rejection of orthodoxy is less than complete, some elements of what would become a more Keynesian position are developed. In particular, a preoccupation with the management of the balance of payments and the need for capital controls as a macroeconomic management tool, considerably before Keynes and White's plans led to the Bretton Woods agreement. In the process it is clear that Prebisch developed several ideas that are still relevant to understand cyclical fluctuations in the periphery, and became more concerned with the capacity of taking advantage of cyclical booms to maintain sustained economic growth.
Keywords: B31; E32; E65; 330; Business Cycle; Macroeconomic Policy; History of Economic Thought